A systematic review and meta-analysis of digital application use in clinical research in pain medicine - Shetty, Ashish; Delanerolle, Gayathri; Zeng, Yutian; Shi, Jian Qing; Ebrahim, Rawan; Pang, Joanna; Hapangama, Dharani; Sillem, Martin; Shetty, Suchith; Shetty, Balakrishnan; Hirsch, Martin; Raymont, Vanessa; et al. (Frontiers in Digital Health, 2022)
Pain is a silent global epidemic impacting approximately a third of the population. Pharmacological and surgical interventions are primary modes of treatment. Cognitive/behavioural approaches and interventional pain management strategies have been used to assist with the management of chronic pain. Accurate data collection and reporting treatment outcomes are vital to addressing the challenges faced. We conducted a systematic evaluation of the current digital application landscape within chronic pain medicine. Objective: To consider the prevalence of digital application usage for Chronic Pain management. These digital applications included mobile apps, web apps, and chatbots. Methods: We conducted searches on PubMed and ScienceDirect for studies that were published between 1st January 1990 and 1st January 2021. We included studies that involved the use of digital applications for chronic pain conditions. Only peer-reviewed studies published in English were included. Out of 84 studies initially identified, 38 were included in the systematic review. The AMSTAR guidelines were used to assess data quality. Data were pooled using a random-effects model. The primary outcome was to report the prevalence of digital application usage for chronic pain conditions. We also recorded the type of digital application studied (e.g. mobile application, web application) and, where data was available, the prevalence of pain intensity, pain inferences, depression, anxiety, and fatigue. Results: 38 studies were included in the systematic review and 22 studies were included in the meta-analysis. The digital interventions were categorised to web and mobile applications and chatbots, with pooled prevalence of 0.22 (95% CI -0.16, 0.60), 0.30 (95% CI 0.00, 0.60) and -0.02 (95% CI -0.47, 0.42) respectively. Pooled standard mean differences for symptomatologies of pain intensity, depression, and anxiety symptoms were 0.25 (95% CI 0.03, 0.46), 0.30 (95% CI 0.17, 0.43) and 0.37 (95% CI 0.05, 0.69) respectively. A sub-group analysis was conducted on pain intensity due to the heterogeneity of the results (I2=82.86%; p=0.02). After stratifying by country, we found that digital applications were more likely to be effective in some countries. Conclusions: The use of digital applications in improving pain-related symptoms shows promise, but further clinical studies would be needed to develop more robust applications.